EREG is a risk factor for the prognosis of patients with cervical cancer - Li, Tianye; Feng, Ruijing; Chen, Bingxin; Zhou, Jianwei (Frontiers in Medicine, 2023)
Background: Cervical cancer is now still threatening women’s health around the world. Identifying critical oncogenic molecules is important to drug development and prognosis prediction for cervical cancer patients. Recent studies have demonstrated that epiregulin (EREG) is upregulated in various cancers, which contributes to cancer progression through triggering the EGFR signaling pathway. However, the role of EREG is still unclear now. Methods: In this work, we first conducted a comprehensive biological analysis to investigate the expression of EREG in cervical cancer. Then, we investigated the correlations between EREG expression level and clinicopathological features. Also, we validated the effects of EREG expression on the proliferation and apoptosis of cervical cancer cells Results: Based on the public database, we found that the expression of EREG was higher in advanced cervical cancer samples. Survival analysis showed that EREG was a risk factor for the prognosis of cervical cancer. In vitro experiments demonstrated that EREG knockdown undermined proliferation and promoted apoptosis of cancer cells. Conclusion: EREG is a vital component participating in the progression of cervical cancer, which contributes to hyperactive cell proliferation and decreased cell apoptosis. EREG might be a valuable target for prognosis prediction and drug development of cervical cancer in the future.